O-004 Mapping wall tension, wall shear stress, and aneurysm wall enhancement in 3D. (23rd July 2022) - Raghuram, A; Galloy, A; Nino, M; Sanchez, S; Hickerson, M; Raghavan, S; Samaniego, E
Abstract : Introduction/Purpose: Computational fluid dynamic (CFD) and finite element (FEA) simulations can provide insight into the unique physical environment that precedes aneurysm rupture. Areas subject to decreased mechanical stresses may rupture because of inflammatory changes in the aneurysm wall. Topographic analysis of aneurysm wall enhancement (AWE), wall shear stress, and wall tension in three dimensions may identify aneurysmal compartments more susceptible to rupture. Materials and Methods: Unruptured aneurysms were prospectively imaged with 7T MRI. Aneurysms were segmented on T1 post gadolinium contrast imaging and analyzed with CFD and FEA. AWE normalized to the corpus callosum was mapped in 3D using orthogonal probes to capture the entire aneurysm wall on 7T MRI. The mean value of all probes was defined as the 3D circumferential AWE (3D-CAWE). Aneurysms more enhancing than the corpus callosum (3D-CAWE≥1) were classified as 3D-CAWE+. Contour maps of time-averaged wall shear stress (TAWSS), wall shear stress gradient (WSSG), oscillatory shear index (OSI), and wall tension (WT) were registered and synchronized for compartmental analysis of the aneurysm wall. Five areas of interest from AWE maps were manually probed in all aneurysms: areas of maximal, mean (3D-CAWE), and minimal MRI signal intensities in the dome, the neck, and areas of focal aneurysm wall enhancement (FAWE). Figure 1 Aneurysm blebs were also manually probed in saccular aneurysms. Results: Twenty-six aneurysms (6 fusiform and 20 saccular) were analyzed. 3D-CAWE and 95th percentile WT were positively correlated to aneurysm size (Spearman's rho = 0.416 & 0.657, p=0.034 & p<0.001 respectively). Fusiform aneurysms had a higher 3D-CAWE and 95th percentile WT than saccular aneurysms (p=0.046 & p=0.003 respectively). 3D-CAWE+ aneurysms (N=8) had thicker walls (p=0.008), higher 95th percentile WT (p=0.03) and higher median TAWSS (p=0.045). In saccular aneurysms, WT was significantly lower in the bleb compared to areas of minimal SI (p=0.028). In areas of FAWE, WT and WSSG were significantly lower compared to the neck (p=0.010 & p=0.027 respectively). Conclusions: The pattern of 3D AWE combined with CFD and FEA analysis may identify areas of the wall more likely to grow or rupture. Disclosures: A. Raghuram: None. A. Galloy: None. M. Nino: None. S. Sanchez: None. M. Hickerson: None. S. Raghavan: None. E. Samaniego: None.